Advanced Automotive Fault Diagnosis : automotive technology : vehicle maintenance and repair - Denton, Tom (Routledge, 2017)
"Learn all the skills you need to pass Level 3 and 4 Vehicle Diagnostic courses from IMI, City and Guilds and BTEC, as well as higher levels, ASE, AUR and other qualifications. Advanced Automotive Fault Diagnosis explains the fundamentals of vehicle systems and components and examines diagnostic principles as well as the latest techniques employed in effective vehicle maintenance and repair. Diagnostics, or fault finding, is an essential part of an automotive technician's work, and as automotive systems become increasingly complex there is a greater need for good diagnostics skills. For students new to the subject, this book will help to develop these skills, but it will also assist experienced technicians to further improve their performance and keep up with recent industry developments. - Checked and endorsed by the Institute of to him to ensure that it is ideal for both independent and tutor-based study - Diagnostics case studies to help you put the principles covered into real-life context - Useful margin features throughout, including definitions, key facts and 'safety first' considerations"--Provided by publisher.